Flouting Maxim in Netizen’s Utterance on The Comment Page of Danise Chariesta’s Instagram Account - Mutia Fitri Hanum; Dadang Sudana; R. Dian Dia-an Muniroh (Universitas Muhammadiyah Semarang, 2022)
To achieve the goals of communication, it is important for the participants in every conversation to obey the cooperative principle in order to avoid misunderstanding of interpretation between them. Danise Chariesta is a content creator who is known for her arrogance. She often received a negatif reaction from netizens. This study aims to reveal the types of flouting maxim by netizen in and also the meaning behind their utterances. The researcher used a descriptive qualitative method. Then, to analyze the data, the researchers used Grice’s theory, Cooperative Principles consisting of four maxim types: quality, quantity, relation, and manner. The study revealed the rationales behind maxims flouting which were beneficial to build fun communication and to elaborate more explanations. The result of the research shows that there are 15 data of flouting maxim in comment page. The highest occurrence of flouting maxim in this movie is flouting maxim of quantity and quality with 5 data (33%). Then followed by flouting maxim of relevance with 3 data (20%). Flouting maxim of manner is the highest occurrence of flouting maxim with 7 data (47%). From all the types of flouting maxim that are performed by the characters in the comment page, the most dominant data that appear in the movie is flouting maxim of manner.